Pemberdayaan Masyarakat melalui Inovasi Perencanaan Pembangunan berbasis 4R (Rembug, Rencana, Realisasi dan Rawat) di Desa Cilangkap Kecamatan Wanasalam sebagai Pilar Utama Kebijakan Partisipatif dan Gotong Royong - Ahmad Sururi; Rahmi Mulyasih (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2017)
Participatory development planning and gotong royong in encouraging the strengthening of village officials and empowering rural community through innovation of development planning policy based on the concept of Rembug, Plan, Realization and Rawat is a grand design of development planning by placing society as center of development as well as actor has a major role in village development planning by prioritizing local resources and potential based on local wisdom. The main focus of this dedication is to provide socialization and mentoring both theoretical and practical in the development of the concept of development planning policy based on the concept of 4R namely Rembug, Plan, Realization and Rearing which aims to empower and improve community skills in preparing development planning with priority resources and local potential which are owned. The method used is participatory village assessment and Participatory Learning and Action by emphasizing on the 4R concept of rembug, plan, realization and care. Based on the results obtained from the mentoring are: 1) Cilangkap Village community as a community service partner has a great response and enthusiasm in the process of mentoring development planning. This can be seen from the number of community attendance in the village meeting villagers with an average attendance of 60% of the total number of households in each village; 2) As one of the villages that are still relatively poor, the community's enthusiasm in following the mentoring program needs to be appreciated as part of the community's awareness of the importance of development designed from, by and for the community; 3). The ability of the community to design the development planning through the formation of development planning organizations, independent village survey activities and rembug activities, plans, realiation and care can be run well although with all the limitations owned but not reduce the substance of the growth process of community empowerment and community motivation in the development planning activities.